FUNGSI PERGELARAN WAYANG KULIT DI MONUMEN TIEN SOEHARTO JATEN KARANGANYAR - Sri Harti (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2018)
Monument of Jaten or Monument of Tien Soeharto locates in Getas Village, Jaten Karanganyar. The initial purpose of the monument building was to commemorate the birthplace of RAJ. Siti Hartinah, the wife of President Soeharto. Since 2009, the function of the Monument of Jaten has developed.This place is also used for the performances of young puppeteers. The monument is a promotional event for young puppeteers to be better known by the wider community. The shadow puppet show is finally held every night of Rebo Pon. Puppet shows performed on the monument Jaten may have primary and secondary functions. The primary function is that the puppet are watched by the public so that their beauty or aesthetic elements can be enjoyed. In addition, puppet shows can also provide entertainment for the community. The secondary function is that by holding a puppet show, the values contained in the play performed by the puppeteer are expected to be able to provide students with value for their audience; strengthen the rope of solidarity; and revive the economic turnaround the small traders around it.Keywords: monument, Jaten, puppet show, function.